An outbreak of COVID-19 associated with a recreational hockey game — Florida, June 2020 - Atrubin, D.; Wiese, M.; Bohinc, B. (Morbidity and Mortality Weekly Report (MMWR), 2020)
On June 16, 2020, a recreational ice hockey game was played at an ice rink in the Tampa Bay, Florida, metropolitan area. Teams A and B, each consisting of 11 players (typically six on the ice and five on the bench at any given time), included men aged 19-53 years. During the 5 days after the game, 15 persons (14 of the 22 players and a rink staff member) experienced signs and symptoms compatible with coronavirus disease 2019 (COVID-19)*; 13 of the 15 ill persons had positive laboratory test results indicating infection with SARS-CoV-2, the virus that causes COVID-19. Widespread transmission of SARS-CoV-2 has been documented at a choir practice (1) and at meat processing plants (2,3); however, apart from an outbreak involving 57 infected dancers that has been linked to high-intensity fitness dance classes in South Korea (4) and a cluster of five infected persons at a squash facility in Slovenia (5), few published reports are available regarding transmission associated with specific sports games or practices. In addition, outbreaks of COVID-19 infections among amateur hockey players in the United States have recently been reported in the news.